Synthesis of carbonaceous materials and their use in water treatment - BERRAHAL, Malika (l’Université de Mostaganem, 2024)
This research study presents an academic investigation on the development of a simple, inexpensive, fast, and effective method for synthesising highly expanded graphene. This method utilises thermal shock in an air atmosphere, which allows for simultaneous oxidation, intercalation, and exfoliation to occur within a few seconds. The collected samples underwent analysis using Fourier-transform infrared spectroscopy, X-ray diffraction spectroscopy, and thermogravimetric analyses. A comparative examination was performed at three crucial temperatures (750°C, 820°C, and 870°C), together with microwave-assisted exfoliation. The results showed the efficacy of the thermal shock technique in facilitating swift and substantial expansion of the graphene structure by augmenting the internal forces within an exceptionally brief timeframe. In addition, the samples that were prepared showed exceptional thermal stability, as well as a remarkable ability to retain green malachite (98%) and alizarine red (up to 100%). Single network hydrogel beads and microwave-assisted exfoliated graphene were successfully synthesized and tested for the elimination of Cefalexin from aqueous solutions. The Langmuir model accurately describes adsorption isotherms, with high correlation coefficients and maximum adsorption capacity of 217.39 mg/g and 209.46 mg/g for the hydrogel network and MWGO respectively. The thermodynamic analysis showed exothermic and spontaneous adsorption. This highlights the potential of graphene-based materials in addressing water pollution and scarcity challenges.
Keywords: graphene, Synthesis, Thermal shock, Thermal stability, Filtration, Retention, Adsorption